Vitamin C Intake and Risk of Prostate Cancer: The Montreal PROtEuS Study - Parent, Marie-Elise; Richard, Hugues; Rousseau, Marie-Claude; Trudeau, Karine (Frontiers in Physiology, 2018)
Background: Vitamin C is a reducing agent and free radical scavenger, acting as antioxidant in plasma membranes and within cells. Based on these properties, a role for vitamin C in cancer incidence has been suspected. There are as yet few large population-based studies focusing on prostate cancer, with the preponderant evidence leaning towards the absence of an association. Nevertheless, many previous studies overlooked prostate cancer aggressiveness, as well as screening and detection issues, which could bias potential associations. Methods: The Prostate Cancer and Environment Study (PROtEuS) is a population-based case-control study conducted in Montreal, Canada. In-person interviews, conducted with 1,916 histologically-confirmed prostate cancer cases and 1,985 population controls, elicited information on a wide range of socio-demographic, lifestyle, and medical factors, including PSA screening. Usual frequency of consumption of 63 food items two years prior to diagnosis/interview was collected, along with use of dietary supplements. Odds ratios (OR) and 95% confidence intervals (CI) between vitamin C intake and prostate cancer were estimated using logistic or polytomous regression, adjusting for potential confounders. Results: We observed no association between dietary intakes of vitamin C (OR for upper vs. lower tertile: 0.95, 95%CI 0.77, 1.18), estimated using the residual method to account for energy intake, or between regular use of vitamin C supplements and/or multivitamins (OR 0.90, 95%CI 0.76-1.05), and overall prostate cancer. Analyses considering disease aggressiveness, or restricted to subjects recently screened with PSA, thereby limiting the potential for undiagnosed cancers in non-cases, generated results consistent with those from the main analyses. Conclusion: Our findings document the absence of an association between recent dietary vitamin C intake, or supplementation, and prostate cancer incidence overall or prostate cancer grade at diagnosis. Based on this, and other available evidence, vitamin C intake does not seem to hold promises with regard to prostate cancer prevention.